(3GdZQI aj GdcdGe Ydi HjJ GdEHQIs - (3YHO GdQMef GdaGSjs
(3ChdgG (B:s
(3bGd GdabjQ eQJLi GdZaQGf jOYi HaGSj YGHO GdQMef hgGA fXekG jhLH GdeSQI ajeG JVefg HjJ GdEHQI s
(3BNQgG (B:s
(3aGdTeS ai XeFgG hEf NQL Yfg HTF eG RhGdgG GHJgL hgPg caGjI ai GdebUO hGdMeO ddg Gdhdi GdeQTO GfJgJ HMeO Gddg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs